Fabrication of High Quality Thin Film of PPV Derivative Polymers Using a Spincoating Method - F. Fitrilawati; M.O. M.O. Tjia; J. Ziegler; C. Bubeck (Indonesian Journal of Physics, 2001)
We report in this work the results of fabricating high quality MEH-PPV and MEH-PPB thin films using spincoating method by proper choice of a solvent, weight concentration and spinning speed. It is found that the films prepared from toluene solutions of weight concentration around 5 % at spinning speeds of 2000 rpm show the highest quality of uniform thickness of d = 540 nm for MEH-PPV and d = 450 nm for MEH-PPB with normalized surface roughness (Ra/d) of 0.3 % for MEH-PPV and MEH-PPB.